2000
DOI: 10.1046/j.1468-1331.2000.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological effects of oral high‐dose methylprednisolone in acute optic neuritis and multiple sclerosis

Abstract: The immunological effects of high-dose methylprednisolone in attacks of multiple sclerosis and acute optic neuritis have only been examined in a few randomized, controlled trials. We studied immunological changes in 50 patients with optic neuritis or multiple sclerosis who underwent lumbar puncture before and 1 week after completing a 15-day course of oral high-dose methylprednisolone treatment. Treatment resulted in a decrease in the concentration of myelin basic protein, a decrease in the serum concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 45 publications
3
33
0
Order By: Relevance
“…33 Furthermore, MBP in CSF is a response biomarker of the effect of treatment with methylprednisolone, and patients with high CSF concentrations of MBP have a better response to methylprednisolone. 34,35 It is tempting to speculate that the decreases in MBP concentrations could reflect the pathological observation of a shift from a white matter demyelinating pathology to a cortical-based pathology, where demyelination is present but less intense than in the white matter, but this hypothesis must be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…33 Furthermore, MBP in CSF is a response biomarker of the effect of treatment with methylprednisolone, and patients with high CSF concentrations of MBP have a better response to methylprednisolone. 34,35 It is tempting to speculate that the decreases in MBP concentrations could reflect the pathological observation of a shift from a white matter demyelinating pathology to a cortical-based pathology, where demyelination is present but less intense than in the white matter, but this hypothesis must be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…30 Glucocorticoids have many effects on the immune system.31 Their effects on the blood-brain barrier can be seen as attenuation of gadolinium enhancement and correlate with macrophage infi ltration into the multiple sclerosis lesions in the brain.32,33 Glucocorticoids interact negatively with transcription factors that have a role in T-cell activation and can induce apoptosis of activated T cells34,35 and diminish the expression of CD26 on CD4+ T cells.36 High doses of methylprednisolone induce expression of transforming growth factor beta, which inhibits production of proinfl ammatory cytokines by effector T cells.37,38 Also, the decline in IgG synthesis seen after treatment with high doses of oral methylprednisolone could be implicated in the clinical response. 39 An additive or synergistic effect of glucocorticoids and interferon beta could be mediated by the ability of glucocorticoids to increase the sensitivity of T cells to interferon beta and upregulate interferon receptors. These effects have anti-infl ammatory potential, mediated by increased production of interleukin 10 and suppressed secretion of interferon gamma by T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we and others reported results from therapeutic studies with potent synthetic CD26/DP IV inhibitors that were initiated in immune disorders (6 -8, 21). The rationale to target CD26/DP IV in diseases with an autoimmune pathogenesis is based on results from previous studies showing elevated numbers of CD26 ϩ CD4 ϩ T cells present in peripheral blood and cerebrospinal fluid from patients with MS (13)(14)(15)(16)(17)(18). In addition, myelin-specific CD4 ϩ T cell clones from patients with MS express high levels of surface CD26/DP IV (45).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, it has been concluded that CD26/DP IV may have a protective role in autoimmune inflammation. In contrast, recent reports found elevated numbers of CD26 ϩ CD4 ϩ T cells in peripheral blood and cerebrospinal fluid from patients with multiple sclerosis (MS), and suggested that CD26/DP IV mediates T cell recruitment to airways in a rat asthma model (12)(13)(14)(15)(16)(17)(18). Moreover, in vitro and in vivo studies conducted with potent synthetic inhibitors identified CD26/DP IV as a target for immunosuppressive therapy (4,19,20).…”
mentioning
confidence: 98%